PERFORMANCE EVALUATION OF ELECTRICAL CHARACTERISTICS OF BIFACIAL HALF-CUT PERC MONOCRYSTALLINE PV MODULES UNDER OUTDOOR CONDITIONS IN NAWABSHAH CITY - Muhammad Moosa Jakhrani,; Abdul Sattar Saand,; Faheem Ahmed Solangi,; Muhammad Ishaque,; Zuhebullah Soomro,; Faisal Zardari, (Spectrum of Engineering Sciences, 2025)
Electrical characteristics of both front and rearside of bifacial photovoltaic modules are normally examined at standard test conditions and rarely at outdoor environments. This work was carried out to inspect the electrical properties (front and rearside) of bifacial half-cut PERC mono-crystalline photovoltaic modules in Nawabshah city’s opened environment. This study measured the PV module's power output (P), open-circuit voltage (Voc), short-circuit current (Isc), maximum voltages (Vmax), maximum current (Imax). Weather parameters included global solar radiation (Ir), ambient temperature (Ta), wind speed (Ws), and relative humidity (Rh). A light meter (HD-2302) was used to measure the amount of global solar radiation that struck the site's horizontal surface, while PROVA AVM-05 was used to record the ambient temperature (Ta), wind speed (Ws), and relative humidity (Rh). Also via the PV analyzer PROVA-1101, the electrical properties of the PV modules both (front and rear) sides were recorded from 09:00 to 16:00 hours at an interval of 15-minutes. The average Ir, Ta, Ws and Rh were found 842.4W/m2, 29.7°C, 3.0m/sec and 46.0%respectively during study period. The PV module's average Pmax, including both the front and back sides, was 334.6W, with the rearside alone producing 27.6W. It is established form the study that the front side produced around 91% of output power and the rest is contributed by its back-side during analysis period at the same operational and environmental conditions.